Assessing the Psychometric Properties of the Persian Version of the Integrative Health and Wellness Assessment Scale in Patients With Type 2 Diabetes - Batoul Alizadeh Taghiabad; Maryam Rassouli; Fateme Jafaraghaee; Zahra Abbasi Ranjbar; Saman Maroufizadeh; Saeed Doaee; Zahra Taheri- Ezbarami (Journal of Holistic Nursing and Midwifery)
Introduction: The role of a nurse coach is to meet the needs of patients for health and wellness, and the theory of integrative nurse coaching is a basis for nurse coaching interventions to support health promotion. Objective: Due to the lack of a valid questionnaire to evaluate the effectiveness of nurse coaching interventions according to this theory in Iranian patients with diabetes, this study aims to assess the psychometric properties of the Persian version of the integrative health and wellness assessment (IHWA) scale in patients with type 2 diabetes. Materials and Methods: This is a methodological study. Participants were 202 patients with type 2 diabetes, who were selected using a convenience sampling method. The process of psychometric evaluation and cross-cultural adaptation was carried out based on the six-step model of Beaton et al. First, using the forward-backward translation method, the original version was translated into Persian. The process of matching the translations was done and a Persian version was prepared. Then, it was back translated into English, which was approved by the developers of the main version. The face validity, content validity, construct validity (using confirmatory factor analysis [CFA]), and convergent validity (using the 12-item short form survey [SF-12]) were assessed. To determine the reliability of the questionnaire, the test re-test reliability (using intra-class correlation coefficient [ICC]) and internal consistency (using Cronbach’s α) were measured. Results: The content validity ratio (CVR) was 0.96 for the whole scale, and the subscale content validity index (CVI) value was 0.97, which are favorable. The results of CFA showed the good fit of the eight-factor model (χ2/df=1.92; CFI=0.91; RMSEA=0.068, SRMR=0.081). The factor loads ​​of all items were significant. The Cronbach’s α for the whole scale was 0.889 and the ICC was 0.833. Conclusion: The Persian version of the IHWA scale with 36 items is a valid and reliable tool and can be used to measure the health and wellness of Iranian patients with type 2 diabetes.